2013
DOI: 10.1177/8756087913503652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of clay and zinc oxide nanoparticles on oxygen barrier properties of polypropylene sheet

Abstract: The oxygen permeation properties of polypropylene nanocomposites were examined to compare their oxygen-barrier performance as affected by temperature (25-50 C), relative humidity (0-50% RH), and nanoparticle contents. Polypropylene/clay, polypropylene/ZnO composites and polypropylene/clay/ZnO ternary nanocomposites were prepared with different compositions by melt compounding to determine the optimum amount of nanoparticles. The results showed that at low temperatures, the effect of both clay and ZnO nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…The second peak of T m2 occurred at a lower temperature and represented the formation of a disordered crystalline form of PLA, as reported by Zhang et al [42]. The Χ c values of the PLA/OC5 and PLA/OC5/ ZnO5 nanocomposites were lower than that of neat PLA, similarly observed by Atayev et al [43]. These authors suggested that the reduction in Χ c was due to the nano-fillers restricting crystalline growth, thereby slowing down the crystallization rate.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 75%
See 1 more Smart Citation
“…The second peak of T m2 occurred at a lower temperature and represented the formation of a disordered crystalline form of PLA, as reported by Zhang et al [42]. The Χ c values of the PLA/OC5 and PLA/OC5/ ZnO5 nanocomposites were lower than that of neat PLA, similarly observed by Atayev et al [43]. These authors suggested that the reduction in Χ c was due to the nano-fillers restricting crystalline growth, thereby slowing down the crystallization rate.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 75%
“…According to the WVP results, the barrier property was enhanced regardless of the decreased crystallinity. This indicated that an extended tortuous path length, arising from the homogeneously dispersed OC or OC/ZnO, dominated the permeability coefficient instead of the crystallinity of PLA [43].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…22 and Atayev and Oner. 23 Throughout the literature cited above, we note that there are no studies that discuss the theoretical analysis of roll-over-web coating of viscous fluid containing nanoparticles. Here, the objective is to formulate the flow mechanism of the roll-over-web coating of viscous fluid containing different nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of radical scavengers suppressed the bacterial effect of ZnO-coated films against E. coli, potentially implicating that the ROS generation in ZnO nanoparticles played an important role in the antibacterial properties of ZnO nanoparticles. Except for the report by Atayev et al [82], whose samples may have excellent antibacterial properties due to the strong photocatalytic effect of ZnO, the results of other studies should have indicated no effective antibacterial activity. In conclusion, the results obtained from this present work demonstrated significant improvement in the overall performance of PBAT and MPBAT nanocomposites.…”
Section: Resultsmentioning
confidence: 94%